Complexation and Antimicrobial Study of Cobalt(II), Nickel(II) and Copper(II) Metal Ions with Nitrogen and Oxygen Containing Schiff Base - Kumari1, Rachana; Rai2, B.K. (Asian Journal of Chemistry, 2014)
Transition metal complexes of the composition [M(BHQH)2X2]; where M = Co(II), Ni(II) and Cu(II); BHQH = 2-butyl-[3-(hydroxy propyl)]-3,1-(4H)-quinazoline-4-hydrazone, X = NH3, pyridine, a, b, g-picolines have been prepared. The complexes have been characterized by molar mass, elemental analyses, molar conductance, magnetic moment, electronic, I.R. spectral studies. On the basis of above studies the ligand (BHQH) is suggested to acts in a bidentate manner and coordination takes place through azomethine nitrogen and oxygen atom of hydroxyl group after deprotonation. The remaining coordination sites are occupied by neutral molecules such as NH3, pyradine, a, b, g picolines. The Co(II), Ni(II) complexes have proposes octahedral geometry whereas, Cu(II) complexes were proposed to have distorted octahedral geometry. in vitro the synthesized compounds were screened against E. coli by disc diffusion method.